Political Will Sebagai Kunci Sukses Implementasi SITANJAK Analisis Studi E-Government Di Kota Pekanbaru - Amansyah, Denny (Socio-political Communication and Policy Review, 2026)
The implementation of e-government at the local level requires strong political commitment and sufficient financial support to ensure its effectiveness. This study aims to analyze the role of political will and financial support in the successful implementation of the Electronic Document Management System (SITANJAK) in Pekanbaru City. The research method applied is qualitative with a case study approach, focusing on the analysis of policy documents, official government reports, and relevant literature on e-government. The findings indicate that political will from the local government is the primary driver in establishing regulations, strengthening governance, and fostering inter-agency coordination in SITANJAK implementation. Meanwhile, financial support plays a vital role in providing technological infrastructure, enhancing human resource capacity, and ensuring system sustainability. The synergy between political commitment and budget allocation is proven to be the key to the success of SITANJAK implementation as part of Pekanbaru’s e-government strategy. This study concludes that the sustainability of e-government programs is highly dependent on consistent political will and adequate financial support. Abstrak Implementasi e-government di tingkat daerah membutuhkan komitmen politik dan dukungan finansial yang kuat agar dapat berjalan efektif. Penelitian ini bertujuan untuk menganalisis peran political will dan dukungan finansial dalam kesuksesan penerapan Sistem Informasi Tata Naskah Elektronik (SITANJAK) di Kota Pekanbaru. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi kasus, melalui analisis dokumen kebijakan, laporan resmi pemerintah daerah, serta literatur terkait e-government. Hasil penelitian menunjukkan bahwa political will dari pemerintah daerah menjadi faktor utama yang mendorong lahirnya regulasi, penguatan tata kelola, dan koordinasi antarinstansi dalam penerapan SITANJAK. Sementara itu, dukungan finansial berperan penting dalam penyediaan infrastruktur teknologi, peningkatan kapasitas sumber daya manusia, serta keberlangsungan operasional sistem. Sinergi antara komitmen politik dan alokasi anggaran terbukti menjadi kunci keberhasilan